DYSPHEMIA COMMENTS ON X : FORM, FUCTION, AND IMPACT ON DIGITAL POLITICAL POLITICAL DISCOURSE - EVI BAKO; Mhd Pujiono (Universitas Negeri Medan, 2026)
This study aims to analyze the form, function, and impact of dysphemia in the comments section of Joko Widodo's X account, the 7th former President of Indonesia. Dysphemia, as a form of coarse or derogatory language, is often used by netizens in political discussions on social media, especially X. This study uses a qualitative approach with thematic analysis to identify patterns of dysphemia that emerge, understand the purpose of its use, and evaluate its impact on digital political dynamics. Data was collected through documentation of comments on Joko Widodo's active X account, particularly those discussing the issue of “Jokowi's fake diploma.” The results show that dysphemia appears in the form of words and phrases that can be classified based on Allan & Burridge's (2006) theory. The forms of dysphemia found consist of: 1). Metaphors, 2). Understatement, 3). Hyperbole, 4). Flippancy, 5). Jargon, 6). Part-whole and one-for-one substitutions, and 7). Abbreviations. Meanwhile, the functions of dysphemia found in the comments section of Jokowi's X account include: 1). to insult, 2). to offend, 3). to express and represent something or a condition that is very bad, 4). to emphasize, 5). to show anger, and 6). to describe the identity of a group.